"Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Papan Kompetisi Bangun Datar (Pakom Bantar) TerhadapPemahaman KonsepMatematika" - Ningrum, Erna Fitria (Prosiding University Research Colloquium, 2021)
The The purpose of this study was to determine the effect of the Problem Based Learning model assisted by the flat wake competition board media on the understanding of Mathematical concepts for fourth grade students at Banaran 2 State Elementary School. This research is a type of Pre-Experimental Design research, with the One Group Pretest-Posttest Design model. Samples had taken as many as 20 students used as an experimental class. The sampling technique used saturated sampling. Data collection used the test method. This test is used to test the extent to which students experience changes in understanding of Mathematical concepts before and after being treated. The analysis used in this study is the Wilcoxon Signed Rank Test with SPSS version 23.0. The results showed the Problem Based Learning model assisted by the flat wake competition board media influense the understanding of Mathematical concept. Evidence of an increase in students understanding of Mathematical concept is a significant difference between the pretest score and the posttest score, the average pretest score 0f 60.71 while the posttest score is 76.60. This is supported by the existence of a hypothesis test conducted with the Wilcoxon Signed Rank Test, the Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). based on the results of the analysis and discussion there was an increase of 15.89 from the average results of the preest and posttest. The results of this research can be concluded that the use of Problem Based Learning model assisted by the flat wake competition board media has a significant effect on the understanding of Matematical concepts on the theory circumference and area of a flat shape.